Facile synthesis of two-dimensional copper terephthalate for efficient electrocatalytic CO2 reduction to ethylene. Issue 1 (20th July 2021) - Zhang, Ying; Li, Yangmei; Tan, Qiang; Hong, Song; Sun, Zhenyu
Abstract: Electrochemical CO2 reduction (ECR) powered by renewable electricity is reckoned to provide an effective strategy to alleviate environmental issues and energy crisis, enabling a potential carbon neutral economy. To boost the ECR to fuels and value-added chemicals, the design of highly active and selective catalysts is important. In this study, we demonstrate facile ultrasonication-facilitated synthesis of two-dimensional copper terephthalate for efficient ECR. High faradaic efficiencies (FEs) of up to 72.9% for hydrocarbons are achieved at a mild overpotential in an H-type cell. In particular, the FE for ethylene (C2 H4 ) formation approaches 50.0% at an applied potential of −1.1 V (vs. the reversible hydrogen electrode), outperforming commercial Cu, Cu2 O, CuO, Cu(OH)2 and many recently reported Cu-based materials. The C2 H4 partial geometric current density is as high as ∼6.0 mA·cm −2 . This work offers a simple avenue to developing advanced electrocatalysts for converting CO2 into high-value hydrocarbons.